Enzymatic and chemical deinking of mixed office wastepaper and old newspaper : paper quality and effluent characteristics - C.K.Lee; Darah Ibrahim; Ibrahim Che Omar; Wan Daud Wan Rosli (2011)
Enzymatic and chemical deinking not only significantly influence the optical and mechanical properties of deinked paper, but also influence the pulp properties and wastewater effluent generated. Both enzymatic and chemical deinking of mixed office wastepaper (MOW) and old newspaper (ONP) showed improvement in brightness (1.4-4.7 units),tensile index (1-14%), burst index (1.2-308%), freeness (1.9%-2.9%), andresidual ink removal (31.1-51.2%) but caused loss in opacity (0.1-2.6%) and tear index (0.1-9.6%). Chemical Oxygen Demand (COD) analysis indicated that effluent produced from enzymatic deinking were about 33.9% and 33.8% lower compared to chemical deinking of ONP and MOW, respectively. Meanwhile, Biological Oxygen Demand (BOD5) obtained from enzymatic deinking of MOW and ONP were 47.1% and 39.3% lower compared to the chemical deinking process, respectively.The result obtained in this work demonstrated that the quality of the pulp and paper obtained from enzymatic deinking process was better than thatfrom the chemical deinking process. This suggests that enzymatic deinking has high potential as an alternative to the chemical method.